2005
DOI: 10.1002/pam.20116
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and intellectual property: The influence of institutional forces on university patenting

Abstract: Over the past 20 years, the number of patents assigned to universities has increased dramatically. This increase coincided with several policy initiatives, such as the Bayh-Dole Act of 1980, designed to foster technology transfer between universities and the private sector. This paper examines the effect of such policies using an institutional framework, designed to illustrate how factors both from inside and outside of academia influence the decision to patent university research. We find passage of the Bayh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
0
21
1
Order By: Relevance
“…In USA, the number of successful patent applications has increased from 517 in 1980 to 3289 in 1995 (Morgan et al, 2001). Furthermore, growth can also be observed in Slovenia (Table 2) Regardless of the fact that the final decision on knowledge research and dissemination remains in the hands of researchers at universities and public research institutes (in terms of publications or patents), studies have shown (Dai et al, 2005) that researchers' decisions are affected both by characteristics of the university environment and the wider society, as well as by policies. Therefore, it can be established that patenting activity is indirectly or directly influenced by two main groups of factors: internal at the level of the researcher and external at the level of universities and the level of the wider environment (country).…”
Section: Figure 1: the Conceptual Theoretical Model Of Researchers' Pmentioning
confidence: 99%
See 4 more Smart Citations
“…In USA, the number of successful patent applications has increased from 517 in 1980 to 3289 in 1995 (Morgan et al, 2001). Furthermore, growth can also be observed in Slovenia (Table 2) Regardless of the fact that the final decision on knowledge research and dissemination remains in the hands of researchers at universities and public research institutes (in terms of publications or patents), studies have shown (Dai et al, 2005) that researchers' decisions are affected both by characteristics of the university environment and the wider society, as well as by policies. Therefore, it can be established that patenting activity is indirectly or directly influenced by two main groups of factors: internal at the level of the researcher and external at the level of universities and the level of the wider environment (country).…”
Section: Figure 1: the Conceptual Theoretical Model Of Researchers' Pmentioning
confidence: 99%
“…In the spirit of marketing, the latter are moving towards "entrepreneurial organizations" (Dai et al, 2005). According to Etzkowitz (2003), these changes can be partially attributed to a new competitive way of funding and the adjustment (expansion) in orientations (e.g.…”
Section: Developing the Model And Key Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations